(901) Analysis of A Two-Channel Queuing Model (A Simulation Approach) تحليل نموذج صف انتظار ثنائي القناة (نهج المحاكاة) - Al Walid El Shafei. (INP., 2024)
This study investigates a queueing system with two servers in a nervous facility, with customer arrivals and service times following specific distributions. The arrival times are independently and normally distributed with a mean corresponding to scheduled times . The system operates under a first-come-first-served queue model, where the first available server handles the next arriving customer. The goal of the study is to estimate the average waiting time, maximum waiting time, and the standard error of the average waiting time.